Sistem Pemeringkat Otomatis Berbasis Kata Sifat - Faisal Rahutomo; Diana Mayangsari Ramadhani; Inggrid Yanuar Risca Pratiwi (Jurnal RESTI (Rekayasa Sistem dan Teknologi Informasi), 2019)
This paper exposes a novel method has been developed during these 2 years. The method is named as “adjective based automatic rating system”. This method is developed to utilize the abundant availability of text on the internet for quality and performance rating purpose. The text is processed in such a way and leave only the adjectives. Semantic analysis is done by two knowledge: adjectives of performance definition and Indonesian adjectives database with its synonym-antonym relation. This research proposes several formula steps, therefore the method output is a rating score that can be tunned its scale. The experiment results have been gathered for several objects: tourism, courier service, and organization performance. With detail information in tourism object experiment, this paper cites the other experiment results as well. This paper also provides availability information of the method as Python library. The results show a high correlation score, always more than 0.9. The results also show acceptable error scores, never more than 45%.